Robust active control based milling chatter suppression with perturbation model via piezoelectric stack actuators. (1st April 2019) - Zhang, Xingwu; Wang, Chenxi; Liu, Jinxin; Yan, Ruqiang; Cao, Hongrui; Chen, Xuefeng
Highlights: The dynamic equations are established and simplified for robust controller design. The perturbation modeling of modal and milling parameters are built and analyzed. The robust active controller is designed for milling chatter suppression. The effectiveness and robustness of the designed controller are verified. Abstract: Milling, as the most widely used processing method, plays an important role in advanced manufacturing. However, milling chatter has severely restricted the development of advanced manufacturing industry. Therefore, it is of great theoretical significance and application value to study the active control of milling chatter. This paper focuses on the design of robust controller for chatter suppression. At first, the milling dynamic equations with active control force are established and simplified with the approximate linear time-invariant model for robust controller design. Then, the perturbation modeling of modal parameters and milling parameters are built and analyzed. Based on the perturbation models, the control algorithm is designed. The numerical simulation in milling process verifies the effectiveness of the designed controller. In order to validate the practical effect, the flank milling and end milling tests are implemented, respectively. The experimental results show that the designed algorithm is able to suppress chatter greatly and lead to the better workpiece surface, which prove the effectiveness and robustness of the designed controller.